2012
DOI: 10.1039/c2cc17607f
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of chemically modified α-Al2O3 particles for high performance ZIF-8 membrane on a macroporous tube

Abstract: Through deposition of APTES-functionalized Al2O3 particles onto a coarse macroporous support, a new strategy to reduce the pore size and simutaneously promote a high density of heterogeneous nucleation sites was developed, and a continuous and thin ZIF-8 membrane exhibiting remarkably high H2 permeance of 5.73 × 10(-5) mol m(-2) s(-1) Pa(-1) and H2/N2 ideal selectivity of 15.4 was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(105 citation statements)
references
References 30 publications
2
103
0
Order By: Relevance
“…In the last ve years, more and more effort has been paid to the preparation of ZIF-8 membranes by in situ growth, secondary growth, and also the liquid phase epitaxy method. [16][17][18][19][20][21][22][23][24][25]33 However, it was oen found that separate ZIF-8 crystals or islands rather than continuous layers were formed on the native ceramic supports by direct solvothermal synthetic routes because heterogeneous nucleation of ZIF-8 crystals on the support surfaces was very poor. 17,26 Therefore, seed coating 20,21 or chemical modication 17,26 of the supports have been applied to promote the heterogeneous nucleation of ZIF-8 crystals on support surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In the last ve years, more and more effort has been paid to the preparation of ZIF-8 membranes by in situ growth, secondary growth, and also the liquid phase epitaxy method. [16][17][18][19][20][21][22][23][24][25]33 However, it was oen found that separate ZIF-8 crystals or islands rather than continuous layers were formed on the native ceramic supports by direct solvothermal synthetic routes because heterogeneous nucleation of ZIF-8 crystals on the support surfaces was very poor. 17,26 Therefore, seed coating 20,21 or chemical modication 17,26 of the supports have been applied to promote the heterogeneous nucleation of ZIF-8 crystals on support surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 45 membrane technology offers superior economics compared to 46 conventional separation techniques, and it is estimated that the 47 use of membranes can decrease energy costs by as much as 30% 48 when compared with conventional, energy intensive technologies 49 [1]. The cost-effectiveness of membrane technology is attributed to 50 the ability to allow gasses to be treated in a single stage/phase as 51 opposed to the multiple stages (pressurizing, depressurizing and 52 purging) needed for conventional pressure swing adsorption 53 systems or different phases (gas and liquid), which are common 54 in commercialized cryogenic separation methods. 55 Despite their economic advantages, membrane technologies 56 are not as widely used as other gas separation techniques due to 57 manufacturing challenges.…”
Section: Q2mentioning
confidence: 97%
“…Reports on the surface modification of -183 alumina are available. In fact, -alumina supports have been 184 modified with ZIF organic ligands [47], a polymer [48][49][50][51][52][53][54], or a 185…”
Section: Q2mentioning
confidence: 99%
“…38 With increasing ZIF loading amount, the relative selectivity of hydrogen to methane/carbon dioxide can exceed 100. In addition, compared to the VACNT supported thin ZIF-8 membrane in this study, thin ZIF membranes show a higher gas permeance with similar or higher hydrogen selectivity, such as alumina supported ZIF-90, ZIF-7 and ZIF-8 membranes, 32,33,39 and polymer supported ZIF-8 membranes. 28 Hydrogen permeance of those membranes is higher than 10 27 mol m 22 s 21 Pa 21 , with the hydrogen relative selectivity larger than 10.…”
mentioning
confidence: 98%